2023
DOI: 10.3390/toxics11020196
|View full text |Cite
|
Sign up to set email alerts
|

Successful Use of Continuous Veno-Venous Haemodialysis in a Case of Potential Lethal Caffeine Intoxication

Abstract: Here we describe the case of a potentially lethal caffeine intoxication after the reported ingestion of 10 g of caffeine. Due to hemodynamic instability with tachycardia and hypertension with an insufficient effect of continuous labetalol infusion, the patient was started on continuous veno-venous haemodialysis (CVVHD). After successful treatment for 15 h, CVVHD could be discontinued, and the patient was discharged home the next day. This case report is the first to report the use of CVVHD as a haemodialysis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…found that the LD 50 of caffeine was about 10 gm/day, which could be equivalent to drinking 100 cups of instant coffee. High chronic exposure to caffeine (<400 to 600 mg/day) has been linked with some dysfunctions including gastrointestinal, muscles, liver, and kidney [19,20] …”
Section: Introductionmentioning
confidence: 99%
“…found that the LD 50 of caffeine was about 10 gm/day, which could be equivalent to drinking 100 cups of instant coffee. High chronic exposure to caffeine (<400 to 600 mg/day) has been linked with some dysfunctions including gastrointestinal, muscles, liver, and kidney [19,20] …”
Section: Introductionmentioning
confidence: 99%